Depresi Mahasiswa Ditinjau dari Keberfungsian Keluarga dan Quarter Life Crisis : Penelitian - Sulis Mariyanti; Lita Patricia Lunanta; Aisyah Ratnaningtyas (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The pressure faced by college students in the digital era has become increasingly complex. Not only are they expected to be independent and succeed academically and in their careers, but they also often experience social pressure due to peers’ success shared on social media. This can trigger feelings of inferiority, anxiety, and even depression. One of the main factors contributing to depression in early adulthood is the inability to cope with life transitions, commonly referred to as a quarter-life crisis. In addition, family functioning also plays a crucial role in supporting students' mental health. This study aims to examine the simultaneous influence of family functioning and quarter-life crisis on the level of depression among university students. The research employs a quantitative approach with a causal design. The sampling technique used is purposive sampling, involving 231 student respondents from various regions in Indonesia. The measurement tools include the Family Functioning Scale adapted from the Family Assessment Device (FAD) by Epstein, Baldwin, and Bishop (1983), consisting of 52 valid items with a Cronbach’s Alpha reliability of 0.950; the Quarter-Life Crisis Scale, based on the theory of Alexandra Robbins and Abby Wilner (2001), consisting of 26 items with a reliability of 0.856; and the Depression Scale using the standardized Beck Depression Inventory-II (BDI-II) by Beck (1991).The results show that, simultaneously, family functioning and quarter-life crisis have a significant effect on students' depression levels, with a significance value of 0.000 (p < 0.05). Partially, family functioning has a negative effect on depression (p = 0.000 < 0.05), meaning that the better the family functioning, the lower the level of student depression. However, partially, the quarter-life crisis does not have a significant effect on depression, with a significance value of 0.405 (p > 0.05).